Use elimination to solve is a clue. It's just a fancy way of saying get rid of a variable (x or y) from one of the equations.
x/3 + 4y = 30 and 2x - y= 5.
Because the coefficients of y are nice I chose to get rid of it from one of the equations.
This step is called rearranging the equation.
2x -y =5
So what next? Here is the elimination part. We replace the y in x/3 + 4y=30 with (2x-5) because they are equal. (y=2x-5)
We have now have x/3+4(2x-5)=30. This looks a lot messier but we can simplify things. There are lots of ways of proceeding from here.
x/3 looks nasty - to get rid of it multiply every term (peice of the equation) by 3
Next thing not to like about the equation is the brackets - essentially we want to count all the x's together. Getting rid of brackets is called multiplying out brackets. It looks strange but is just a property of the number system
12(2x-5) is identical to 12*2x - 12*5 or 24x-60 in other words we can replace 12(2x-5) by 24x - 60
we now have
counting the x's together
solving for x
Because we know x we can find y by substuting x=6 in 2x-y=5 (for example - you could use x/3 - 4y=30 but 2x-y=5 looks easier)
Hope this helped - there's quite a lot of distractions in the question such as multiplying out etc.